2011
DOI: 10.2478/v10007-011-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous estimation of ramipril, acetylsalicylic acid and atorvastatin calcium by chemometrics assisted UV-spectrophotometric method in capsules

Abstract: In the present work, three different spectrophotometric methods for simultaneous estimation of ramipril, aspirin and atorvastatin calcium in raw materials and in formulations are described. Overlapped data was quantitatively resolved by using chemometric methods, viz. inverse least squares (ILS), principal component regression (PCR) and partial least squares (PLS). Calibrations were constructed using the absorption data matrix corresponding to the concentration data matrix. The linearity range was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…[5] Also can be used for the descriptive issue solving like the model composition, identification and understanding. Chemometrics shows its application in the multivariate data collection and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Also can be used for the descriptive issue solving like the model composition, identification and understanding. Chemometrics shows its application in the multivariate data collection and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that very few analytical methods like UVSpectroscopy and HPLC methods were reported and no chemometric method was reported for the analysis of the above said combination. [11][12][13][14][15][16][17][18][19][20][21][22][23] Moreover, most of the proposed methods demand complex extraction procedures for the separation of drugs in to individual components from the dosage form Thus the present study aims to design chemometric assisted spectroscopic methods for the intricate analysis of Atorvastatin and Aspirin without prior separation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a literature survey exposed there were numerous analytical methodologies to detect ASP and SA in tablets and biofluids [6][7][8][9][10][11][12][13][14][15][16][17] . Particularly, for the pharmaceutical industry, the interest raises on the need of developing robust analytical stability methods to ensure drugs will not degrade until the sell-by date has expired [18,19] .…”
mentioning
confidence: 99%
“…However, with the introduction of multicomponent methods, UV spectrophotometry showed an astonishing capability in the quantitation of compounds in mixtures without previous separation [8][9][10][11][15][16][17]24] . This aspect revealed great advantage over HPLC methods, such as lower cost, less time of analysis and minimum organic solvent waste.…”
mentioning
confidence: 99%